(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
The efficient crystallization conditions for high temperature synthesis of sodium-cerium(III) orthophosphate from binary molten salts have been investigated in a light of influence of the inert reaction media addition. Taking into consideration NaF and Na2MoO4 as an addictives to a convention phosphate melt the crystallization regions of CePO4 and Na3Ce(PO4)2 have been identified by means of IR spectroscopy and powder X-Ray diffraction methods. The initial Na/P ratio in the melt has been shown to play the key role in pure Na3Ce(PO4)2 phase formation. The concentration of NaF has been chosen as 20–60 mol. % and MoO3 in a range of 30–60 mol. %, while the cerium(III) content has been maintained equal to 10 mol. %. Additional application of NaF or Na2MoO4 lowers the temperature from 1400 in comparison to Na4P2O7 flux to 1000°C and homogenization time from 12 to 1h., respectively. Thus, the optimal conditions for the high-temperature growth has been found to be Na/P = 1.67 and NaF content equal to 30–45% mol. in case of fluoride-containing systems, and Na/P> 4,00 with MoO3 content of 25–36% mol for a molybdate one. In case of both fluoride and molybdate addition the crystallization region of the target compound has been bordered by a wide area of CePO4 phase. Three crystallization regions has been estimated during crystallization process: CePO4, Na3Ce(PO4)2 and a wide field of their co-crystallization. With Na/P ratio in the binary melt there is a simultaneous change in the solids structure prepared. Thus, when CePO4 possesses highly condensed CeO8 polyhadra in the framework and crystallizes at lower Na/P ratio, Na3Ce(PO4)2 corresponds to isolated CeO8 moieties that are stabilized under higher Na/P values. Within the synthetic conditions investigated, the melts have shown to play a depolymerizing role for the phosphate chains found in the melt, leading to crystallization temperature lowering in initial melt. The approach proposed for the of Na3Ce(PO4)2 synthesis allows to expand the temperature range of its formation and to carry out its uniform doping with fluorescent activators to modify its characteristic spectrum for the needs of modern inorganic LEDs.